Analysis of electrical circuits supplied by sequence of impulses. Issue 2 (13th July 2020) - Georgiev, Zhivko; Trushev, Ivan
Abstract : Purpose: This paper aims to analyze transient and steady state processes in series resistive capacitive-circuits when the supplied voltage is a sequence of periodic rectangular pulses. The purpose is to obtain an analytical formula for the capacitor voltage at any instant of time, both for the transient and the steady-state processes. Design/methodology/approach: The main approach is to use a combination of differential and recurrence equations. Findings: An analytical expression (formula) for obtaining the capacitor voltage at any instant of time has been found. Originality/value: The results obtained are new. They are much more convenient to use than the results obtained by the Fourier series. The exposed approach can also be used in other circuits and other forms of the supplied voltage.